New insight into the protective effect of Citrullus colocynthis loaded with ZnONP cream on glutaraldehyde-induced dermatitis in health care workers - Walaa A. Ali; Walaa A. Moselhy; Marwa A. Ibrahim; Ahlam G. Khalifa; Gadallah Mohamed (Scientific Reports)
Abstract Glutaraldehyde (GLU) is mainly used in medicine by healthcare workers during infection control as a chemical disinfectant. It has been linked to numerous health hazards that range from asthma to irritation of the eye to contact dermatitis. Citrullus colocynthis (C.C.) is utilized as a supplement to combat a range of health-related problems. This study aimed to assess the effectiveness of locally applied Citrullus colocynthis extract and Citrullus colocynthis loaded with ZnONPs against dermatitis caused by the disinfectant glutaraldehyde (2%).The female mice were divided into five groups (G1, G2, G3, G4, and G5). Group 1 was used as a control. The other 4 groups (2,3,4,and 5) were sprayed with 2% GLU (2 mg/kg body weight), and the other groups (3,4,and 5) were subjected to local application of natural products (Citrullus colocynthis extract cream, ZnONP cream, and Citrullus colocynthis loaded on ZnONP cream), respectively. Each experimental animal was followed for 5 days per week for 30 days.Our findings revealed that GLU-induced dermatitis via the upregulation of TNF-α, IL-1b, NFkb 1, and ptgs2 mRNA expression and the downregulation of TGFB1 mRNA expression caused oxidative stress and altered the biochemical markers and histological appearance. However, these effects were improved by the ZnONPs, C.C. extract, and C.C.-ZnONPs.Local application of Citrullus colocynthis ZnONPs and ZnONPs had preventive effects against GLU-induced dermatitis through the suppression of oxidative stress and inflammatory markers and the enhancement of antioxidants.